Differences in Immune Response During Competition and Preparation Phase in Elite Rowers - Bizjak, Daniel Alexander; Treff, Gunnar; Zügel, Martina; Schumann, Uwe; Winkert, Kay; Schneider, Marion; Abendroth, Dietmar; Steinacker, Jürgen Michael (Frontiers in Physiology, 2021)
Background: Metabolic stress is high during training and competition of Olympic rowers, but there is a lack of biomedical markers allowing to quantify training load on the molecular level. We aimed to identify such markers applying a complex approach involving inflammatory and immunologic variables. Methods: Eleven international elite male rowers (age 22.7±2.4 yrs; VO2max 71±5 mL•min-1•kg-1) of the German National Rowing team were monitored at competition phase (COMP) vs. preparation phase (PREP), representing high vs. low load. Perceived stress and recovery were assessed by a Recovery-Stress-Questionnaire for Athletes (RESTQ-76 Sport). Immune cell activation (dendritic cell (DC)/macrophage/monocytes/T-cells) was evaluated via fluorescent activated cell sorting. Cytokines, High-Mobility-Group-Protein B1 (HMGB1), cell-free DNA (cfDNA), creatine kinase (CK), uric acid, and kynurenine were measured in venous blood. Results: Rowers experienced more general stress and less recovery during COMP, but sports related stress and recovery did not differ from PREP. During COMP, DC/macrophage/monocyte and T-regulatory cells (Treg-cell) increased (P=0.001 and 0.010). HMGB1 and cfDNA increased in most athletes during COMP (P=0.001 and 0.048), while CK, uric acid, and kynurenine remained unaltered (P=0.053, 0.304, and 0.211). Pro-inflammatory cytokines IL-1β (P=0.002), TNF- (P<0.001), and the chemokine IL-8 (P=0.001) were elevated during COMP, while anti-inflammatory Il-10 was lower (P=0.002). Conclusion: COMP resulted in an increase in biomarkers reflecting tissue damage, with plausible evidence of immune cell activation that appeared to be compensated by anti-inflammatory mechanisms such as Treg-cell proliferation. We suggest an anti-inflammatory and immunological matrix approach to optimize training load quantification in elite athletes.